Hur blir en litteraturvetare litteraturdidaktiker? - Sofia Wijkmark; Christina Olin-Scheller (Tidskrift för Litteraturvetenskap, 2022)
How can a Literary Scholar be Transformed Into a Literary Didact?: A Case Study on Competence Provision and Competence Development